Analisis Manajemen Berbasis Sekolah Dalam Pelaksanaan Mutu Pendidikan di MTS Negeri 2 Medan - Muhammad Muhammad; Syaiful Bahri (UMSU, 2020)
This study focuses on the analysis of school-based management in the implementation of education quality in MTs Negeri 2 Medan related to planning, organizing, evaluating the values of school-based management that are autonomy, flexibility, participation, transparency and accountability. The purpose of this study was to analyze planning, organizing, evaluating School Based Management in the implementation of Quality Education in MTs Negeri 2 Medan. The research approach used is a qualitative approach with the type of data collection through observation, interviews, documentation and triangulation.The results of this study, school-based management planning in improving the quality of education can be seen by doing identification first to see the potential and readiness of madrasah and madrasah citizens in implementing SBM which is focused on handling activities or learning process activities in the fields of teaching, teachers, student development, finance. and community relations. School-based management organizations in the implementation of quality education include the grouping of SBM components, establishing an authority structure, formulating and establishing methods of procedures and SBM facility providers based on agreed planning using the principle of justice, with the intention of distributing tasks based on the capacity and professionalism of personnel. . Evaluating SBM in the implementation of the quality of education is the evaluation or assessment of teachers which are usually prioritized on individual teacher achievements, especially in teaching and learning activities, and their participation in educational activities in schools. The supporting factor for the implementation of SBM at MTs Negeri 2 Medan is the participation of the community, both parents and committees in school activities and teachers who almost all meet academic qualifications. Meanwhile, the inhibiting factors are the lack of solicitation to parents regarding the planning of the MBS program and the lack of understanding of parents regarding SBM and the presence of students who are not orderly about school regulations.